1995
DOI: 10.1093/geronb/50b.2.p114
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Binocular Vision: Detection of Noise-Masked Targets in Young and Old Observers

Abstract: This study investigated the effects of age on binocular unmasking. This term denotes the fact that a visual signal embedded in noise is detected appreciably better when the stimulus complex contains interocular cues (dichoptic condition) than when such cues are absent (binoptic condition). Detection thresholds for two Gabor signals differing in spatial frequency were determined in young and old adults with no identifiable ocular pathologies. The signals were embedded, in both conditions, in two-dimensional Gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…Nevertheless, the current results are similar to those reported by Pardhan et al, who found no age difference in (two-dimensional) equivalent noise at 6 c /deg. Using a different masking paradigm from the one used here, Speranza et al 34 also found no age difference in equivalent noise at 1.5 and 3 c /deg.…”
Section: Discussionmentioning
confidence: 50%
“…Nevertheless, the current results are similar to those reported by Pardhan et al, who found no age difference in (two-dimensional) equivalent noise at 6 c /deg. Using a different masking paradigm from the one used here, Speranza et al 34 also found no age difference in equivalent noise at 1.5 and 3 c /deg.…”
Section: Discussionmentioning
confidence: 50%
“…Because the stereograms are generated by computers, it is p possible to create dynamic patterns of binocular disparity that change over time. One can also manipulate perceptually important variables, such as the type and magnitude of noise (see, e.g., Speranza, Moraglia, & Schneider, 1995). t Given the many advantages of random-dot stereograms, it is surprising that they have not typically been used by researchers interested in aging and stereopsis (see, e.g., Bell, Wolf, & Bernholz, 1972;Haegerstrom-Portnoy, Schneck, & Brabyn, 1999;Hofstetter & Bertsch, 1976;Jani, 1966;Wright & Wormald, 1992).…”
mentioning
confidence: 99%
“…Specifically, we have shown (Moraglia & Schneider, 1990, 1994Schneider, Moraglia, & Jepson, 1989;Speranza, Moraglia, & Schneider, 1995;see, also, Henning & Hertz, 1973, 1977 that the detectability ofa visual sigThis research was supported by grants to G.M. and B.S.…”
Section: Binocular Unmaskingmentioning
confidence: 79%
“…Conversely, the highest signal-to-noise ratio would occur in this same channel when the Gabor is presented in counterphase to the two eyes. Finally, it is assumed that there is some internal noise in each of these disparity channels, so that detection cannot occur at infinitesimally small values of contrast and there is some degree of interocular jitter that will interfere somewhat with perfect summation (Speranza et al, 1995).…”
Section: F(et/) = G(et/)[2 + 2cos(2ired Xg)]'mentioning
confidence: 99%